Architectures and implementations for speech enhancement - Coşgül, Gökhan. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2000., 2000)
Complexity of a high performance speech enhancement algorithm has been reduced while retaining its quality. This modification leads to faster implementation as well as lower cost.The reduced complexity speech enhancement algorithm has taken as a typical digital signal processing application. Thus, architectures and implementation techniques for blocks involved in this algorithm have been studied. In addition, thanks to the design methodology employed, these implementations can easily be ported into other algorithms involving the same blocks.
Keywords: Signal processing -- Digital techniques.; Fourier transformations.